Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1088/0960-1317/23/10/105005
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a side aligned optical fibre interferometer by focused ion beam machining

Abstract: Focused ion beam (FIB) machining is a promising technique for the fabrication of micro-optical components with high quality surface finishes. In this work, a prototype of a side aligned optical fibre interferometer was successfully fabricated by the three-dimensional deterministic FIB machining technique. A highly accurate 45• reflective mirror with surface roughness (Ra) of 10 nm has been successfully fabricated at the centre of the fibre to direct the core guided light to the side of the fibre. A surface top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Except for the literature mentioned above, Sun et al [ 90 ] proposed a prototype of a fiber-side microcantilever fabricated by a three-dimensional deterministic FIB machining technique. As shown in Figure 11 , a deep groove was machined in the top of a single-mode fiber, which formed a Fabry–Perot cavity.…”
Section: Other Microcantilever Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the literature mentioned above, Sun et al [ 90 ] proposed a prototype of a fiber-side microcantilever fabricated by a three-dimensional deterministic FIB machining technique. As shown in Figure 11 , a deep groove was machined in the top of a single-mode fiber, which formed a Fabry–Perot cavity.…”
Section: Other Microcantilever Sensorsmentioning
confidence: 99%
“…Different from ref. [ 90 ], Li employed a ps-laser to produce the deep groove with high-speed material removal, while the microcantilever surface and the 45° reflective mirror was still machined by FIB milling to obtain a smooth optical surface. The performance test indicated that the side-microcantilever accelerator has an acceleration measurement range from 0 g to 6 g with a resolution of 0.01 g.…”
Section: Other Microcantilever Sensorsmentioning
confidence: 99%
“…It has also been effectively used to cleave and polish the fiber endfacet [131][132][133][134][135][136][137]. In addition, FIB machining has been employed for fabricating lab-aroundfiber and lab-in-fiber devices such as microgratings [138][139][140][141][142][143][144][145][146][147][148][149][150], microcavities [151][152][153][154][155][156][157][158][159][160], as well as access holes and channels [161][162][163][164][165][166][167][168][169]. It is worth mentioning that the beam shaping structures fabricated on the fiber tip predominate in FIB applications in optical fibers (figure 7).…”
Section: Lof Technologymentioning
confidence: 99%
“…Furthermore, a side aligned optical fiber interferometer was experimentally demonstrated by Sun et al using FIB milling [159]. A high beam current of 50 nA at 30 kV was used to remove huge volume of the fiber material to create a high aspect-ratio (∼20:1) cavity for sensing.…”
Section: Microcavitiesmentioning
confidence: 99%